2018
DOI: 10.1038/s41379-018-0083-x
|View full text |Cite
|
Sign up to set email alerts
|

Association of tumor-infiltrating T-cell density with molecular subtype, racial ancestry and clinical outcomes in prostate cancer

Abstract: The inflammatory microenvironment plays an important role in the pathogenesis and progression of tumors and may be associated with somatic genomic alterations. We examined the association of tumor infiltrating T-cell density with clinical-pathologic variables, tumor molecular subtype and oncologic outcomes in surgically-treated primary prostate cancer occurring in patients of European-American or African-American ancestry. We evaluated 312 primary prostate tumors, enriched for patients with African-American an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
106
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(124 citation statements)
references
References 52 publications
(67 reference statements)
17
106
0
1
Order By: Relevance
“…[15][16][17][18][19] Clinical outcomes and the potential mechanisms involving PCa and TIICs have been widely reported. Kaur et al 20 marked the T cells in PCa tissues with CD3, CD8, and FOXP3 immunostaining and revealed that ERG activity and PTEN loss were affected by the high proportion of T cells, but clinical outcomes showed no association with these results. Petitprez et al 21 reported that a high proportion of CD8 + T cells could lead to a greater risk of advanced development of PCa patients with node metastasis.…”
mentioning
confidence: 99%
“…[15][16][17][18][19] Clinical outcomes and the potential mechanisms involving PCa and TIICs have been widely reported. Kaur et al 20 marked the T cells in PCa tissues with CD3, CD8, and FOXP3 immunostaining and revealed that ERG activity and PTEN loss were affected by the high proportion of T cells, but clinical outcomes showed no association with these results. Petitprez et al 21 reported that a high proportion of CD8 + T cells could lead to a greater risk of advanced development of PCa patients with node metastasis.…”
mentioning
confidence: 99%
“…Intra-tumoural heterogeneity in the immune microenvironment has been described in numerous epithelial cancer types, both within primary lesions and between different metastatic sites 7,[11][12][13][14][15] . In breast cancer, a vTMA methodology was used to demonstrate that agreement between TMA and whole tumour assessment of TIL burden plateaued when sampling any more than four 0.6mm cores 23 .…”
Section: Discussionmentioning
confidence: 99%
“…It is now known that the presence or absence of immunerelated factors such as tumour-infiltrating lymphocytes (TIL) can serve as powerful prognostic and/or predictive biomarkers across a range of cancer types [7][8][9][10] . TMAs continue to be frequently employed in studies that seek to investigate the potential role of TILs as putative biomarkers 7,[11][12][13][14][15] . The success of such studies is dependent on the ability of the TMA approach to capture a sufficiently representative picture of the immune phenotypes present within the wider tumour.…”
Section: Introductionmentioning
confidence: 99%
“…The most novel finding from this study is that PTEN-deficient prostate tumors exhibited increased IDO1 protein expression and had higher FoxP3+ Treg density, suggesting expansion of immunosuppressive factors in PTEN-deficient prostate cancer 159,160 . Although mechanistic studies are needed to assign causal associations, it can be A study conducted on 312 primary prostate cancer specimens showed that high FoxP3+ Treg cell density was not associated with clinicopathological features but was significantly associated with earlier biochemical recurrence and prostate cancer metastasis 81 .…”
Section: Discussionmentioning
confidence: 99%
“…The immune-cell landscape of tumors that harbor PTEN somatic mutations is complex and highly heterogeneous, with studies showing that PTEN deficiency is linked to high CD8+ T-cell density 66,81 while others exhibit inverse correlations with this cell type [82][83][84] (Table 1).…”
Section: Pten Loss and Immune Cell Infiltrationmentioning
confidence: 99%